Constitutional judges - Figueroa Gutarra, Edwin (2016)
This study develops the importance of constitutional justice of the Judiciary as an exclusive task, considering that law is evolving and therefore requires expertise. Furthermore, the jurisdictional treatment of fundamental rights requires certain skills that the governing bodies of the Judiciary are in the need to identify, promote and consolidate. The defense of the principles, values and guidelines underlying the constitutional State is also the task of judges and is a categorical imperative for these ones to join such material duties.